Prienų šnektos sprogstamųjų priebalsių spektro sklaida ir kitos skiriamosios ypatybės - Jaroslavienė, Jurgita (Baltistica, 2010)
THE SPECTRA AND OTHER DISTINCTIVE FEATURES OF PLOSIVE CONSONANTS IN THE SUBDIALECT OF PRIENAIEvery plosive consonant has a similar impact on both the beginning (when preceding a vowel) and the end (when following a vowel) of the spectrum of respective vowels. Second and third formant differences of consonants have special prominence, including their initial position in the spectrum and the dynamics of adjacent vowel formant beginnings, as well as intensity, height and shortness of their spectra.In the articulation of voiced plosive consonants a significant role is played by friction and voice. At the moment of plosion, vibrations are distributed throughout a wider range of frequencies compared with the pronunciation of respective voiceless consonants. The main role in the pronunciation of voiceless plosive consonants belongs to the source of noise or friction. They are characterised by a pause and a burst of low energy which is seen in spectrograms as a certain kind of a column. It is the widest in the case of the consonants [k] and [k̑], and the narrowest – with [p] and [p̑].The labial plosives [p] and [p̑] are pronounced with the least noise;regarding the qualitative differences of adjacent vowels, it is possible to attribute these sounds to the class of low sounds. Concerning the voiced consonants, the least intense and lowest ones are [b] and [b̑] respectively. When comparing [p], [p̑] and [b], [b̑], it should be noted that they differ in sonority;a slightly lower pitch is typical of the voiced consonants respectively. These labial plosives differ clearly from other plosives in the height of their pitch, i.e. as low consonants from high ones.The front-tongue consonants [t] and [t̑] are more intense sounds in comparison with [p] and [p̑];regarding the spectrum of their adjacent vowels, it is possible to attribute them to the class of high sounds. Respectively, the voiced consonants [d], [d̑] are also more intense than the labial [b], [b̑]. Besides, voiced sounds differ from their voiceless correlates [t] and [t̑] in sonority, yet [d] and [d̑] are more intense and have a slightly lower pitch than [t] and [t̑] respectively. Regarding the spectral dispersion of adjacent sounds, it should be noted that the hard consonants [t] and [d] noticeably increase the pitch of adjacent back vowels at their beginning and the end respectively.The most intense consonants in the subdialect of Prienai are the front-tongue (front-palate) and mid-tongue (mid-palate) sounds [k] and [k̑], as well as [g] and [g̑];they are also attributable to high-pitch consonants, except for being compact sounds. As in the case of [t] and [d], the hard [k] and [g] also noticeably increase the height of pitch in the articulation of adjacent back vowels.It should be noted that the spectra of respective voiced and voiceless plosives are similar, except for the fact that at word-initial positions, the spectrum of voiceless consonants is much more dispersed and not so prominent from the moment of plosion until the beginning of sonority because vocal folds do not vibrate during the pronunciation of a voiceless consonant.Palatalised plosive consonants differ from their counterpart hard plosives in the height of pitch: the following plosives of raised pitch should be regarded as sharp consonants: [b̑], [d̑], [g̑], [p̑], [t̑] and [k̑]. Pitch height differences are particularly noticeable between [k] and [k̑] as well as [g] and [g̑].The duration of plosive consonants has been noticed to be related to the place of consonant articulation: the shortest duration in the subdialect is typical of labial plosives. Perhaps the obstruction caused by speech organs at the front of the mouth is overcome faster than the one existing deeper in the mouth cavity.The prominence of aspiration depends both on the type of the syllable and adjacent consonants, their type, etc. The clearest aspiration is found with short stressed and circumflex syllables. Aspiration is also amplified by a penultimate consonant of the same type, i.e. a plosive (nulùpkʽ ~ nulùpk ‘please peel’).Experimental investigation of the plosive consonant spectra has shown that phonological peculiarities and distinctive features of [p], [p̑], [t], [t̑], [k], [k̑], [b], [b̑], [d], [d̑], [g] and [g̑] are determined by the initial or final part of the spectrum of adjacent vowels, the duration, intensity and height of consonant spectrum. Plosive consonants are especially different in the character of dynamics that the second and the third formants in the initial or final sections of adjacent vowels possess, as well as in the tempo of shifting and in the position in their spectrum.The strongest impact of all the plosive (and other) consonants is on the initial or final section of the formants of adjacent vowels. For example, the influence of palatalised and non-palatalised consonants on the adjacent vowels is increasingly stronger the closer the vowel stands to the consonant.
Keywords: eksperimentinė fonetika; lietuvių dialektologija; Prienų šnekta; sprogstamieji priebalsiai; spektras; spektro sklaida; skiriamosios ypatybės